O Lugar e o Tempo - projecto de reabilitação de um lote na rua do Farol - Jorge Costa Vilalta Canudas (2019)
As a student of architecture, I have always felt that the role of the architect in society is to organize the space for the qualitative development of human relationships. This dissertation arose from the desire to rehabilitate an ilha in Foz do Douro, with an unique social context disturbed by the circumstance itself. This curiosity was expanded to the whole lot ending up with an heterogeneous set of houses and a narrow path that crosses it. Therefore, the object of this essay encompasses different types of buildings, with distinct social dynamics, and their own interactions with the city, which requires specific and complex answers. The privileged location of the object, inside the urban area of Foz, has attracted tourism and real estate interest, so the simple rehabilitation of the existing volumes would be an unrealistic solution for the place's potential. On the other hand, apart from the will to keep its original identity and memory, the primary concern was to give this place with better living conditions back to the families who have always lived there. Faced with a context where different realities intersect, the architectural project is explored as a strategic process, academic but realistic, able to meet the contemporary needs of the city, to the detriment of the purely speculative and deterministic intervention. As a link between academia and the professional world, the search for an intervention strategy that addresses these problems, has shown me how to move from an abstract exercise to a real context, and the confirmation that the function of architecture is to shape people's lives.